Word, providence and mercy in the Joseph Narrative - Sanz Giménez-Rico SJ, Enrique (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2018)
The final chapters of the book of Genesis (Gn 37-50) present the Joseph Narrative, probably one of the most well-known and studied stories of the Old Testament in recent years of biblical research. Starting from many of the assertions and proposals of this research, the current article focuses on one aspect of the narrative: the sending of Joseph by Jacob in search of his brothers out of interest for their situation and life, and in order to pass on to his father word on these. Joseph though is only able to fulfil part of the mission, because his brothers prevent him from bringing his news back to his father. A thorough consideration of the meaning and value of this obstruction in the story of Gn 37-50 and its understanding within the framework of the providential presence and action of God in these chapters allows a drawing of the connections that are present in the Joseph Narrative between providence, mercy and the protectionof the assaulted.